Individual Differences in Automatic Emotion Regulation Interact with Primed Emotion Regulation during an Anger Provocation - Zhang, Jing; Lipp, Ottmar V.; Hu, Ping (Frontiers in Psychology, 2017)
The current study investigated the interactive effects of individual differences in automatic emotion regulation (AER) and primed emotion regulation strategy on skin conductance level (SCL) and heart rate during provoked anger. The study was a 2 × 2 (automatic emotion regulation tendency [expression vs. control] × priming [expression vs. control]) between subject design. Participants were assigned to two groups according to their performance on an emotion regulation-IAT (differentiating automatic emotion control tendency and automatic emotion expression tendency). Then participants of the two groups were randomly assigned to two emotion regulation priming conditions (emotion control priming or emotion expression priming). Anger was provoked by blaming participants for slow performance during a subsequent backward subtraction task. In anger provocation, SCL of individuals with automatic emotion control tendencies in the control priming condition was the lower than those with automatic emotion control tendencies in the expression priming condition. However, SCL of individuals with automatic emotion expression tendencies did no differ in the automatic emotion control priming or the automatic emotion expression priming condition. Heart rate during anger provocation was higher in individuals with automatic emotion expression tendencies than in individuals with automatic emotion control tendencies regardless of priming condition. This pattern indicates an interactive effect of individual differences in automatic emotion regulation and emotion regulation priming on SCL, an index of emotional arousal. Heart rate was sensitive to the individual differences in automatic emotion regulation. This finding has implications for clinical studies of the use of emotion regulation strategy training suggesting that different practices are optimal for individuals who differ in automatic emotion regulation tendencies.